Dampak Struktur Aset, Struktur Modal dan Profitabilitas terhadap Nilai Entitas - Rajagukguk, Lenni; Syahzuni, Barlia Annis (Jurnal Riset Akuntansi Politala, 2024)
The economic and social conditions of a country greatly impact the health of an entity, and not all of them can survive the current economic crisis. The same thing happens to property and real estate entities. Although now this industry can be said to be growing rapidly in Indonesia. However, in 2021, it will become the industrial sector with the largest debt default. This has a huge impact on the value of the entity, which can be seen from changes in share prices. This research is to determine the partial influence of asset structure, capital structure and profitability on entity value. The independent variables use asset structure, capital structure, and profitability. Meanwhile, the entity value is the dependent variable. Entities in the property and real estate sector listed on the Indonesia Stock Exchange (BEI) are the population used. A purposive sampling technique was used to obtain 30 companies according to the criteria in the 2020-2022 period, resulting in 90 research samples. The sample selection criteria used were publishing complete annual financial reports in rupiah, having positive profits, and publishing share prices during the research period. Multiple linear regression analysis is used as a data processing method assisted by statistical data processing software. The results of data analysis show that asset structure has a negative effect on entity value, while profitability and capital structure have a significant effect and have a positive impact on entity value.